2012
DOI: 10.1093/ndt/gfs498
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of cystatin C-based estimates of glomerular filtration rate in kidney transplant recipients: a systematic review

Abstract: The cystatin C-based Le Bricon equation was the most accurate, and most of the cystatin C-based equations showed improvements in 30% and 50% accuracy compared with the creatinine-based MDRD equation. Cystatin C-based equations may offer an advantage over the MDRD equation in kidney transplant recipients. Estimating equations re-expressed with standardized cystatin C have been developed and their accuracy needs to be tested in the kidney transplant population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 39 publications
1
28
0
1
Order By: Relevance
“…The cystatin C-based equations may offer an advantage over the MDRD equation in kidney transplant recipients. [22] The elevated levels of urinary CYSC are associated with interstitial fibrosis and tubular atrophy in renal transplant recipients, and may become a useful tool for monitoring kidney allografts. [23] …”
Section: Cystatin Cmentioning
confidence: 99%
See 1 more Smart Citation
“…The cystatin C-based equations may offer an advantage over the MDRD equation in kidney transplant recipients. [22] The elevated levels of urinary CYSC are associated with interstitial fibrosis and tubular atrophy in renal transplant recipients, and may become a useful tool for monitoring kidney allografts. [23] …”
Section: Cystatin Cmentioning
confidence: 99%
“…The most accurate biomarker for AKI after renal allograft based on Le Bricon equation [22] Fonseca Isabel [34] Tim-3 Allograft survival in recipients treated with anti-Tim-3 monoclonal antibody or antiGal-9 mAb was significantly shorter than that in control recipients. [35] TIM-3 rises as a biomarker for diagnosis acute cellular rejection.…”
Section: Ccl2mentioning
confidence: 99%
“…Although the KDIGO recommendations on kidney transplantation comment the possible interest of using CyC to GFR estimation, they do not advocated its regular clinical use, due to the paucity of validation studies in this group of patients [20] . A recent systematic review [70] , identified 10 studies, evaluating the accuracy of 14 different CyC-based eGFR equations in renal transplant recipients. The authors conclude that the Le Bricon equation [67] was the highest accurate, and the majority of the CyC-based equations exhibited 30% and 50% accuracy improvements compared with the Cr-based MDRD equation.…”
Section: Performance Of Cystatin-based Gfr Estimation Equations In Kimentioning
confidence: 99%
“…Much of this variability is consequence of different study populations, differences in the GFR reference standard measurement, and in variation in the calibrators for the CyC measurement, and this latter contributes to the greatest source of variation. Standardized reference material for CyC has already been developed [71] , but none of the studies involved in this analysis [70] , adopted this methodology. In 2008 a new Cr-and CyC-based formula (CKD-EPI CyC equation) was developed [40] , which besides serum CyC includes the variables of gender, age and race, and seems more accurate than the formulas based on Cr or CyC alone, but this formula requires further testing in various patients groups.…”
Section: Performance Of Cystatin-based Gfr Estimation Equations In Kimentioning
confidence: 99%
“…Globalement, les é quations inté grant la cystatine C semblent apporter une meilleure performance pré dictive, même s'il reste encore à dé montrer que cette amé lioration de pré diction soit cliniquement substantielle [155]. En transplantation cardiaque, l'é quation de Rule et al inté grant la cystatine C permet d'augmenter significativement la justesse de pré diction du DFG par rapport à l'é quation MDRD [84,156].…”
Section: Inte´rêt De La Cystatine C En Transplantationunclassified